2008
DOI: 10.1177/1534734607313699
|View full text |Cite
|
Sign up to set email alerts
|

To the Editor

Abstract: We would like to congratulate our colleagues, Musab U. Saeed and Donald J. Kennedy, on publication of their article "A retained sponge is a complication of vacuumassisted closure therapy." 1 In the August issue of Wounds, we published a similar article about a patient with a chronic fistula in the lower leg 5 years after vacuumassisted closure therapy. 2 On a magnetic resonance imaging scan a 4.5-cm sinus tract was identified. The sinus tract led to a sinus in the center in which a roughly shaped structure was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…(28) Over half of the patients suffered new-onset or worsening infections related to retained dressing pieces. Further studies have demonstrated that bleeding (29)(30)(31)(32)(33)(34), infection or sepsis related to retained sponges (35)(36)(37)(38)(39)(40)(41), and fistula formation (37,(41)(42)(43) are potential complications of NPWT. We sought, therefore, to determine the new-onset complications within 30 days of NPWT initiation in the outpatient versus inpatient settings.…”
Section: Discussionmentioning
confidence: 99%
“…(28) Over half of the patients suffered new-onset or worsening infections related to retained dressing pieces. Further studies have demonstrated that bleeding (29)(30)(31)(32)(33)(34), infection or sepsis related to retained sponges (35)(36)(37)(38)(39)(40)(41), and fistula formation (37,(41)(42)(43) are potential complications of NPWT. We sought, therefore, to determine the new-onset complications within 30 days of NPWT initiation in the outpatient versus inpatient settings.…”
Section: Discussionmentioning
confidence: 99%